Allegories of the Vietnamese Past: Unification and the Production of a Modern Historical Identity - Ariate, Maria Ima Carmela L. (Kasarinlan: Philippine Journal of Third World Studies, 2015)
Review of Allegories of the Vietnamese Past: Unification and the Production of a Modern Historical Identity by Wynn Wilcox (New Haven: Yale University Press)